If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2y + -3) + 3x = 7 Reorder the terms: 2(-3 + 2y) + 3x = 7 (-3 * 2 + 2y * 2) + 3x = 7 (-6 + 4y) + 3x = 7 Reorder the terms: -6 + 3x + 4y = 7 Solving -6 + 3x + 4y = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 3x + 6 + 4y = 7 + 6 Reorder the terms: -6 + 6 + 3x + 4y = 7 + 6 Combine like terms: -6 + 6 = 0 0 + 3x + 4y = 7 + 6 3x + 4y = 7 + 6 Combine like terms: 7 + 6 = 13 3x + 4y = 13 Add '-4y' to each side of the equation. 3x + 4y + -4y = 13 + -4y Combine like terms: 4y + -4y = 0 3x + 0 = 13 + -4y 3x = 13 + -4y Divide each side by '3'. x = 4.333333333 + -1.333333333y Simplifying x = 4.333333333 + -1.333333333y
| 0=2(2x^2-103x+546) | | 4x=x+5+2x-1 | | 4(j+5)=2 | | 13-2=j+6 | | -4(4a-8)= | | -4(4a-7)= | | Y=-12e^2x+36e^4x | | r+0.48=1.6 | | h(t)=-16x^2+85 | | 6(1)-(-7)=13 | | c/3+7=11/2 | | -(1+11n)= | | 6x+3x=1251 | | 5x+11=35 | | 2h+3.4forh=3 | | 5x-3=21-X | | x/2+2/7= | | -4-6m-m=2m-4 | | Y=7(x+870) | | 24x+4(x-2)=10(x+2)+8 | | -4(b-3)= | | 1.50h+9.99=36.99 | | Y+24=-14 | | 10+22xn=98 | | 18-4n=6-16m | | 2(4(5)-12)+3(5)= | | 6+x+3=4x+8 | | b+11/17= | | 0=(5x-2)(x+7) | | (2x+4)+X=10 | | -7(7-6k)= | | 60=4(x-2)+5(8x-4) |